INDUKSI KALUS Gerbera jamesonii DENGAN KOMBINASI NAA DAN BAP - Tantri Swandari; Titin Setyorini (Program Studi Agroteknologi INSTIPER, 2017)
Gerbera, an ornamental flower plant of herbs, has been commonly cultivated as a potted plant or cut flowers. The main problem in conventional propagation Gerbera is insufficient amount of seeds to meet the growing demand of planting material. This study aims to develop effective and low cost in vitro system of Gerbera propagation; therefore Gerbera seeds are available in large quantities and cheaper price. The research was conducted in laboratory of plant tissue culture, Stiper Agriculture Institute, Yogyakarta from March to June 2017. The young leaves Gerbera jamesonii, commonly planted in the Dieng plateau area, were used as explant. The explants were inoculated in solid medium which contain of ¼ MS (Murashige and Skoog), sucrose 30 g/L and combination of NAA (Naphthalene Acetate Acid) and BAP (Benzilaminopurin). The combinations of NAA and BAP were A0B0 (NAA 0 mg/L + BAP 0 mg/L); A1B0 (NAA 1 mg/L + BAP 0 mg/L); A2B0 (NAA 2 mg/L + BAP 0 mg/L); A0B1 (NAA 0 mg/L + BAP 1 mg/L); A2B1 (NAA 2 mg/L + BAP 1 mg/L); A0B2 (NAA 0 mg/L + BAP 2 mg/L); A1B2 (NAA 1 mg/L + BAP 2 mg/L), A2B2 (NAA 2 mg/L + BAP 2 mg/L). It was observed that ¼ MS medium supplemented with NAA and BAP can be used for callus induction from leaf explants of Gerbera jamesonii. Callus began to be induced three to four weeks after planting. Medium with combination of NAA 2 ppm and BAP 1 ppm (A2B1) produced the best characterized callus, with shiny green appearance and clustered form (embryogenic). Keywords : Callus induction, Gerbera jamesonii, NAA, BAP